2021
DOI: 10.3389/fimmu.2021.629917
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod Targets Toxoplasmosis Through Modulating Host Toll-Like Receptor-MyD88 Signaling

Abstract: Toxoplasma gondii is a prevalent parasite of medical and veterinary importance. Tachyzoïtes and bradyzoïtes are responsible for acute and chronic toxoplasmosis (AT and CT), respectively. In immunocompetent hosts, AT evolves into a persistent CT, which can reactivate in immunocompromised patients with dire consequences. Imiquimod is an efficient immunomodulatory drug against certain viral and parasitic infections. In vivo, treatment with Imiquimod, throughout AT, reduces the number of brain cysts while renderin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…Notably, neither of these compounds is able to completely eradicate chronic infection, similar to other recently described compounds that show efficacy in the mouse model of toxoplasmosis 42 . Other recent studies show that modulation of immune responses using the TLR7 agonist imiquimod can reduce chronic infection and suppress subsequent infection by treated bradyzoites in an immunocompetent mouse model 43 . Using a more stringent model for reactivation of chronic infection, it was shown that ATP mimetics that specifically inhibit calcium-dependent protein kinase 1 (CPKD1) both reduce the burden of chronic infection 44 and prevent reactivation in an immunocompromised mouse model of toxoplasmosis 27 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, neither of these compounds is able to completely eradicate chronic infection, similar to other recently described compounds that show efficacy in the mouse model of toxoplasmosis 42 . Other recent studies show that modulation of immune responses using the TLR7 agonist imiquimod can reduce chronic infection and suppress subsequent infection by treated bradyzoites in an immunocompetent mouse model 43 . Using a more stringent model for reactivation of chronic infection, it was shown that ATP mimetics that specifically inhibit calcium-dependent protein kinase 1 (CPKD1) both reduce the burden of chronic infection 44 and prevent reactivation in an immunocompromised mouse model of toxoplasmosis 27 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…At least 50 promising anti-cyst candidates have been identified through screening of compound libraries, target-based drug design, or repurposing of Food and Drug Administration (FDA)approved drugs [see review (78)]. For example, imiquimod has recently been identified as a promising prophylactic and therapeutic drug against brain cyst burden and cyst reactivation through its immunomodulatory role (79). While the discovery of pharmacological cysticidal agents is underway, nutritional therapy has emerged as a new approach to cope with chronic T. gondii infection.…”
Section: Impact Of Plant-based Foods Phytochemicals and Nutrients On ...mentioning
confidence: 99%
“…To improve the predictive translatability of animal models, the nutritional products must be tested in a large sample and in different infection models. Studies involving immunodeficient animal models (e.g., dexamethasone-induced immunosuppression) could also help in determining whether nutrition mitigates the recrudescence of latent CNS infection (79).…”
Section: Translating Research Into Clinical Practice: Obstacles and S...mentioning
confidence: 99%
“…Importantly, treatment with imiquimod, postestablishment of CT, significantly reduces the number of brain cysts, leading to a delay or abortion of reactivation. Molecularly, imiquimod upregulated the expression of Toll-like receptors and activated the MyD88 pathway, resulting in the induction of the immune response to control reactivation [170].…”
Section: Current Treatmentsmentioning
confidence: 99%